A Spelling Course for Students in the Health Technology Bachelor Degree - Miriam Gutiérrez Escobar; Raúl López Fernández; Rosa María Rodríguez Arencibia; Rachel Yanes Seijo; Loreta Sánchez Ortiz; Saimí de la Caridad Risquet Toscano (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Background: As part of control tests taken by students, problems in the use of the language emerged. Therefore, it was uniformly established how to deal with spelling mistakes through the implementation of Instruction 1 / 2009. Objective: To design a spelling course for students in the Health Technology Bachelor Degree. Methods: A descriptive-observational study was conducted from January to March 2010. The sample consisted of 120 first year students. The main methods used were: document analysis, surveys and educational testing. Results: As main causes of spelling mistakes students identified the lack of rules knowledge, the lack of reading habits and little use of the dictionaries. The most frequent mistakes identified in the diagnostic test were: written accent (we are working with Spanish speaking students), changes, omissions or additions and agreement. This course covers a total of 60 hours and emphasizes in six general issues: following the guidelines of Instruction 1 / 2029, starting with a diagnostic test, using a textual approach, promoting mostly practical activities, following productive teaching methods with an emphasis on inductive and deductive procedures and highlighting the systematization of the teaching process as a didactic principle. Conclusions: The design of this course contributes to eliminate spelling mistakes in students.